Lived-Body Experiences in Virtual Reality A Phenomenology of the Virtual Body. - Akbal, Zeynep (Digitale Gesellschaft., 2023)
What is it like to perceive a virtual object through the sensed presence of a virtual body? How do subject-object relations occur and can be actualized in virtual environments? Zeynep Akbal explores the impact of virtual reality (VR) technology on the subjective experience of the body and situates the results in context with existing theories in media sciences and the phenomenology of bodily perception. This study presents VR technology as a tool that can be used to more closely examine and study the fundamental intersections of the humanities and the natural sciences that explore the nature of perception.